Search for massive long-lived particles decaying semileptonically at √s=13 TeV - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (The European physical journal. C, Particles and fields, 2022)
A search is performed for massive long-lived particles (LLPs) decaying semileptonically into a muon and two quarks. Two kinds of LLP production processes were considered. In the first, a Higgs-like boson with mass from 30 to 200 GeV/c2 is produced by gluon fusion and decays into two LLPs. The analysis covers LLP mass values from 10 GeV/c2 up to about one half the Higgs-like boson mass. The second LLP production mode is directly from quark interactions, with LLP masses from 10 to 90 GeV/c2. The LLP lifetimes considered range from 5 to 200 ps. This study uses LHCb data collected from proton-proton collisions at√s=13 TeV, corresponding to an integrated luminosity of 5.4fb-1. No evidence of these long-lived states has been observed, and upper limits on the production cross-section times branching ratio have been set for each model considered.